Soil Sensitivity Index as an Indicator for Climate-Smart Urban ForestrySoil Sensitivity Index as an Indicator for Climate-Smart Urban Forestry - Kašanin-Grubin, Milica; Antić, Nevena; Stojadinović, Sanja; Živanović, Nikola; Rončević, Vukašin; Štrbac, Snežana (Geopauta, 2024)
Concept of climate-smart forestry, designed for mountain forests, was modified and applied to urban forest areas which are under high anthropogenic and climate change pressures. Accordingly, main objective of the UrbanFoS project is to define soil degradation indicators in urban forests under the umbrella of climate-smart forestry concept. It will be done through three steps: 1. determination of key sensitive properties of soil to degradation processes; 2. field and laboratory climate simulations; 3. definition of ecosystem services of urban forests. As the indicators that define the susceptibility of soil to degradation processes are of key importance for urban forest sustainability, the knowledge gained will be used to develop soil degradation index applicable to urban forest soils under climate change conditions.